Study of two-dimensional periodic surface lattices for high-power mm and sub-mm wave Cherenkov devices - Konoplev, I; Cross, A; MacLachlan, A; Phipps, A; Robertson, C; Young, A; Thumm, M; Phelps, A (2011)
Studies of a periodic surface lattice and a surface field oscillator based on such a lattice, producing radiation at high-GHz frequencies are presented. The scalability of the oscillator is discussed. The influence of the structure's parameters on the Cherenkov device's performance is demonstrated. © 2011 IEEE.